2014
DOI: 10.1039/c4ra06511e
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mechanical, thermal and dynamic mechanical properties of functionalized nanoalumina reinforced sulphone ether linked tetraglycidyl epoxy nanocomposites

Abstract: The objective of the present work is to synthesize 1,4′-bis (4-amine-phenoxy) sulphone benzene epoxy resin (TGBAPSB) via 1,4′-bis (4-amine-phenoxy) sulphone benzene (BAPSB) and epichlorohydrin in order to obtain tetra functional epoxy with improved properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 35 publications
2
21
0
Order By: Relevance
“…The density of DGEBA and TETA were 1.15-1.20 g/cm 3 and 0.97-0.99 g/cm 3 , respectively (This was obtained from the manufacturer's test report). Graphite flakes (<20 lm) and 3-aminopropyltriethoxysilane (APTES) were purchased from Sigma Aldrich.…”
Section: Experimental Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…The density of DGEBA and TETA were 1.15-1.20 g/cm 3 and 0.97-0.99 g/cm 3 , respectively (This was obtained from the manufacturer's test report). Graphite flakes (<20 lm) and 3-aminopropyltriethoxysilane (APTES) were purchased from Sigma Aldrich.…”
Section: Experimental Materialsmentioning
confidence: 99%
“…This is attributed to a higher percentage of F-GO having a strong tendency to agglomerate due to increase in viscosity of epoxy resin when mixed with nanoreinforcements. 3…”
Section: Xrd Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The solutions containing DGE and a blank sample were titrated against 0.2 M NaOH. The EEW value of DGE in the solution was determined using equation trueEEW=normalM/normalf(normalB-normalS) …”
Section: Methodsmentioning
confidence: 99%
“…This is mainly due to the realization of the exceptional property enhancement achieved by these materials at low filler contents. Many studies have demonstrated that introduction of well‐dispersed nanofillers into polymer matrixes is very effective in improving their properties, including mechanical and thermal properties, as well as dielectric properties . Wahab et al .…”
Section: Introductionmentioning
confidence: 99%